Effect of sowing dates, seeding rates, awn and flag leaf removal on yield and its components of Adana-99 bread wheat cultivar - Noori, Shang Haseeb Abdulqader (Sulaimani Journal for Pure and Applied Sciences, 2018)
The experiment was performed, to assess the effect of different planting dates (15th Nov. 2015 to 25th Feb. 2016) each 20 days interval, different plant densities (120, 140, 160,180, 200 and 220) kg/ha and different removal treatments (control, awn, flag leaf and both- awn+flag leaf) removal and their interaction on grain yield and yield components of bread wheat cultivar (Adana-99). The experimental arrangement was a (6×6×4) factorial RCBD with three replicates. Grain yield with some of its components was measured such as (spike length, spike weight, number of spikelet/spike, number of grain/spike, weight of grain/spike, 1000- grain weight, harvest index, biological yield and grain yield). The results of grain yield and its components can be summarized as follows: the planting dates significantly affect on these characters, (15th Nov. 2015) showed maximum values for all characteristics with the exception of harvest index produced by (25th Dec. 2015). The result of the effect of plant density on studying characters was significant, plant density 120 kg/ha produced maximum values for all characters with the exception of harvest index recorded by 180 kg/ha, biological yield produced by 220 kg/ha and grain yield recorded by 200 kg/ha. While the effect of removal treatments on yield and its components significantly responded to these effects. The control treatments produced maximum values for all characters with the exception of harvest index produced by both (awn+flag leaf) removal treatments.
Keywords: Wheat; Planting dates; plant densities; removal treatments; yield and its components